Presynaptic A₂A adenosine receptors control CB₁ cannabinoid receptor-mediated effects at the corticostriatal nerve terminals - Ferreira, Samira Cardoso Lopes (2012)
The striatum is the main input nucleus of the basal ganglia, involved in motor control and different forms of learning. Corticostriatal glutamatergic afferents represent the principal excitatory drive to the striatum, and hence, to the whole basal ganglia. Several neurological and psychiatric disorders, including Parkinson's disease, psychosis and addiction, involve non-Hebbian alteration of corticostriatal plasticity; thus, it is important to study the signaling systems which keep these terminals controlled. Dopamine, originated from midbrain areas is the best known signal shaping corticostriatal plasticity. Besides, the intrinsic modulators, adenosine, acting on A2A adenosine receptors (A2ARs), and endocannabinoids, acting on CB1 cannabinoid receptors (CB1Rs), also play key roles in the modulation of corticostriatal neurotransmission. A2ARs and CB1Rs are required for the correct functioning of the basal ganglia and are emerging therapeutic targets in neurological and psychiatric disorders. One of the best examples is the A2AR antagonist, Istradefylline, with the intention to be used as a palliative medicine adjunct to levodopa. Recently, A2ARs and CB1Rs were shown to heteromerize, but the physiopharmacology of this novel signaling entity is controversial. Furthermore, although several reports found both receptors in corticostriatal terminals, their co-localization and functional interaction to control glutamate release has not been investigated. The objective of my thesis work was to study the functional co-localization of A2ARs and CB1Rs in vGlut1-positive, i.e. corticostriatal terminals of the rat and mouse. It was observed that most of the A2ARs in vGluT1-positive terminals colocalize with CB1Rs, which assumes functional interaction. The high co-localization rate between A2ARs and CB1Rs has led to the investigation of possible cross-modulation of the binding properties between the CB1R and the A2AR in striatal synaptic membrane preparation. It was found that the interaction is unidirectional, i.e. A2AR ligands are able to negatively modulate CB1R maximum binding sites or affinity but not vice versa, i.e. CB1R ligands failed to XV significantly affect A2AR binding parameters. This indicates that A2AR ligands may be able to modulate CB1R-dependent mechanisms in corticostriatal terminals. The next task was to assess the neurochemical consequences of the observed interactions. First, the effect of CB1R activation on the K+-evoked, Ca2+-dependent release of [14C]glutamate from striatal nerve terminals of the rat and mouse was established. CB1R activation inhibited the evoked release of [14C]glutamate in accordance with previous reports. According to the above mentioned binding data, the co-administration of A2AR ligands, irrespective of being agonist or antagonist, prevented the inhibitory action of CB1R agonists on the evoked release of [14C]glutamate. Adenosine acting on A2ARs is thought to result from the breakdown of extracellular ATP, which is co-released with glutamate. Thus, it is expected that CB1R activation would also decrease extrasynaptic ATP accumulation in the striatum. Indeed, bioluminescence assay revealed that CB1R activation decreased the K+-evoked release of ATP in striatal nerve terminals. Thus, although at the receptor-receptor level only A2ARs control CB1Rs, CB1Rs are able to indirectly interfere with A2AR functioning by decreasing the release of the adenosine source, ATP. In order to confirm the interaction at the presynaptic level, whole cell patch clamp electrophysiological experiments were carried out in corticostriatal slices from the rat. Two parameters were measured in this experimental paradigm: paired pulse ratio (PPR) which is thought to be a presynaptic phenomenon, and synaptic transmission which may encompass post-synaptic as well as glial mechanism. Therefore, the alterations of the PPR will give the most reliable conclusion about a presynaptic nature of the measured effect. The removal of the majority of extrasynaptic adenosine by adenosine deaminase (ADA) facilitated the CB1R activation-induced increase in PPR, but counteracted the CB1R-mediated depression of corticostriatal neurotransmission. These apparent paradoxical results might be the outcome of the different functions of pre- versus post-synaptic A2ARs in controlling CB1Rs. In addition, since XVI exogenous activation of A2ARs did not recover the effect of CB1Rs on synaptic transmission, it is likely that another adenosine receptor is involved, in particular, the A1Rs. Furthermore, as expected from the above-detailed functional studies, A2AR ligands counteracted the CB1R activation-induced increase in PPR, and also compromised the CB1R-mediated depression of corticostriatal neurotransmission. In conclusion, the data presented in this thesis provide the first evidence for the co-localization of the two major neuromodulator receptors at the corticostriatal terminals. The two receptors interact closely at these terminals, with important functional consequences, which is likely to have therapeutic implications.